2008 3rd IEEE Symposium on New Frontiers in Dynamic Spectrum Access Networks 2008
DOI: 10.1109/dyspan.2008.79
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Cognitive Radio for First Responders

Abstract: Small Form Factor (SFF) Software Defined Radio (SDR) platform is used to implement an experimental cognitive radio for first responders. The system was demonstrated in the 2007 Software Defined Radio technical conference and product exhibition, and is selected for presentation in the demonstrations and experimentation track in the IEEE DySPAN 2008.Different processing tasks are divided between a TI c64x+ DSP and a Xilinx Virtex IV FPGA while an ARM9 core is used to host Greenhills operating system. To tackle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Therefore, a successful transmission can be heard by all nodes, resulting in an upper-bound for detection probability in a realistic environment. Further, we assume the SUs are synchronized to use a DCC and since SUs are provided with wideband front-ends of a software defined radio [12], the overhead of switching between signaling and data communication is negligible.…”
Section: Problem Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a successful transmission can be heard by all nodes, resulting in an upper-bound for detection probability in a realistic environment. Further, we assume the SUs are synchronized to use a DCC and since SUs are provided with wideband front-ends of a software defined radio [12], the overhead of switching between signaling and data communication is negligible.…”
Section: Problem Definitionmentioning
confidence: 99%
“…1. During the sensing period, the broadband channel is divided into a number of subchannels and each SU senses these subchannels using a Filterbank [12], [13]. The signaling period is used to implement the collaborative sensing.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various testbeds [99][100][101][102], prototypes [103][104][105][106][107][108][109] and experiments [110][111][112] have already demonstrated that the DSA/CR vision is not a mere theoretical concept, but a real promising solution. However, many critical aspects still remain open.…”
Section: Motivation and Scopementioning
confidence: 99%
“…However, it can be easily extended to any band, allowing for adaptive protocol development, enhanced QoS, etc. In particular, a software defined radio (SDR) [13] could be implemented allowing capability of using additionally licensed bands for emergency signal relay.…”
Section: Proposed Architecturementioning
confidence: 99%